From battling adult authority to battling the opposite sex: Little Lulu as gag panel and comic book. Issue 4 (1st October 2016) - Abate, Michelle Ann
Abstract : When iconic comics character Little Lulu moved from the Saturday Evening Post, where she had resided since the 1930s, to comic books during the 1950s, her character underwent numerous transformations. One compelling but formerly overlooked change is the nature of Lulu's rebellion. In the single-panel gag comics, the young girl was overwhelmingly targeting adults with her antics. Meanwhile, in the comic books, her sworn enemy is the gang of neighbourhood boys. This modification from intergenerational conflict in the pre-war era to intragenerational ones during the post-war period forms a compelling and previously unexplored facet to the literary, artistic and cultural alterations to this character that took place across different print formats. At the same time, the shift from plots that pitted children against adults in the 1930s to ones that pitted girls against boys in the 1950s reflects larger shifts in American culture regarding the gendering of children and the sexual segregation of childhood. This essay argues that this new focus did far more than merely permit Marge's Little Lulu to tell different stories; it radically altered the aim and intent of Buell's original character along with the commentary on gender, childhood and US culture that it offered.